2009
DOI: 10.1677/joe-08-0194
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiac fatty acids metabolism in transgenic mice overexpressing bovine GH

Abstract: Cardiac energy metabolism depends mainly on fatty acid (FA) oxidation; however, regulation of FA metabolism in acromegalic (Acro) heart is unknown. The aim of the study was to evaluate cardiac expression of key proteins of FA metabolism in young and elder transgenic mice overexpressing bovine GH Acro. Expression of proteins regulating FA entry into the cells, their uptake by mitochondria and beta-oxidation were evaluated by western blot, while FA content by Fourier transform infrared microspectrometry. Regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…In conclusion, our data demonstrated the activation of the extrinsic pathway of cardiac apoptosis in elder acromegalic animals, which are characterized by ventricular hypertrophy (Bohlooly-Y et al 2001) and abnormalities of energetic (Bohlooly-Y et al 2001, Bogazzi et al 2007) and lipid (Bogazzi et al 2009b) metabolism. Interestingly, those changes may, at least partially, revert in young Acro animals during pegvisomant therapy, supporting the concept that changes in energetic metabolism and apoptosis degree might have different impacts on the cardiac function of young and elder animals.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…In conclusion, our data demonstrated the activation of the extrinsic pathway of cardiac apoptosis in elder acromegalic animals, which are characterized by ventricular hypertrophy (Bohlooly-Y et al 2001) and abnormalities of energetic (Bohlooly-Y et al 2001, Bogazzi et al 2007) and lipid (Bogazzi et al 2009b) metabolism. Interestingly, those changes may, at least partially, revert in young Acro animals during pegvisomant therapy, supporting the concept that changes in energetic metabolism and apoptosis degree might have different impacts on the cardiac function of young and elder animals.…”
Section: Discussionsupporting
confidence: 59%
“…1 mg/daily, s.c. for 15 days) as previously reported (Liao et al 2006, Bogazzi et al 2008, 2009b. To exclude any antagonist's proper effect, Wt animals were treated with pegvisomant; in addition, Wt and Acro animals were also treated with vehicle.…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In our cardiomyocytes, aliskiren did not decrease expression of (P)Rr or Igf2/M6Pr receptors, so the angiotensin II-independent effects of a potential renin increase at the cardiac level should perhaps be further considered in relation to clinical treatment. It has also recently been demonstrated that the ERK1/2 pathway activation is involved in regulating cardiac fatty-acid metabolism [82] and in the contraction-induced increase in plasma-membrane CD-36…”
Section: Discussionmentioning
confidence: 99%